The development of a measurement system for fortifying Malaysia’s energy security - Shadman, Saleh (2025)
Energy security (ES) is a complex concept requiring a multifaceted approach to quantify through any set of dimensions, indicators, or variables. For the past two decades, researchers in energy management, policy, and sustainability have studied ES intensively. A critical issue identified in Malaysia is the lack of a consolidated framework and policy documentation for ES. The over-reliance on fossil fuels for energy generation, driven by the need for affordable, always-available energy, often overshadows environmental sustainability. This study's first objective is to create system dynamics models using primary and secondary data to map the most feasible dimensions of Malaysia’s ES. Stakeholder engagement follows to further add input and context to this data, leading to primary data collection that identifies five ES dimensions. These dimensions are then used to create a framework for quantifying ES through indicator mapping, data normalization, and aggregation.